Characterization of Composition and Antifungal Properties of Leaf Secondary Metabolites from Thirteen Cultivars of Chrysanthemum morifolium Ramat - Xue, Huanhuan (Molecules, 2019)
Chrysanthemum morifolium Ramat is an ornamental plant of worldwide cultivation. Like many other species in the family Asteraceae, C. morifolium is a rich producer of secondary metabolites. There are two objectives in this study: (I) to determine and compare the diversity of apolar secondary metabolites among different cultivars of C. morifolium and (II) to compare their properties as antifungal agents. To attain these objectives, we selected 13 cultivars of C. morifolium that are commonly used for making chrysanthemum tea as experimental materials. Leaves at the same developmental stage were collected from respective mature plants and subjected to organic extraction. The extracts were analyzed using gas chromatography–mass spectrometry. A total of 37 apolar secondary metabolites including 26 terpenoids were detected from the 13 cultivars. These 13 cultivars can be largely divided into three chemotypes based on chemical principal components analysis. Next, the extracts from the 13 cultivars were examined in in vitro assays for their antifungal properties against three species of pathogenic fungi: Fusarium oxysporum, Magnaporthe oryzae, and Verticillium dahliae. Significant variability in antifungal activity of the leaf extracts among different cultivars was observed. The 13 cultivars can be divided into four groups based on their antifungal activities, which could be partly correlated to the contents of terpenoids. In short, this study reveals large variations in chemical composition, particularly of terpenoids, of leaf secondary metabolites among different cultivars of C. morifolium and their different abilities in functioning as antifungal agents.